Particulate hydroxy-PAH emissions from a residential wood log stove using different fuels and burning conditions. (September 2016) - Avagyan, Rozanna; Nyström, Robin; Lindgren, Robert; Boman, Christoffer; Westerholm, Roger
Abstract: Hydroxylated polycyclic aromatic hydrocarbons are oxidation products of polycyclic aromatic hydrocarbons, but have not been studied as extensively as polycyclic aromatic hydrocarbons. Several studies have however shown that hydroxylated polycyclic aromatic hydrocarbons have toxic and carcinogenic properties. They have been detected in air samples in semi urban areas and combustion is assumed to be the primary source of those compounds. To better understand the formation and occurrence of particulate hydroxylated polycyclic aromatic hydrocarbons from residential wood log stove combustion, 9 hydroxylated polycyclic aromatic hydrocarbons and 2 hydroxy biphenyls were quantified in particles generated from four different types of wood logs (birch, spruce, pine, aspen) and two different combustion conditions (nominal and high burn rate). A previously developed method utilizing liquid chromatography – photo ionization tandem mass spectrometry and pressurized liquid extraction was used. Polycyclic aromatic hydrocarbons were analyzed along with hydroxylated polycyclic aromatic hydrocarbons. The hydroxylated polycyclic aromatic hydrocarbon emissions varied significantly across different wood types and burning conditions; the highest emissions for nominal burn rate were from spruce and for high burn rate from pine burning. Emissions from nominal burn rate corresponded on average to 15% of the emissions from high burn rate, with average emissions of 218 μg/MJfuel and 32.5 μg/MJfuel for high burn rate and nominal burn rate, respectively. Emissions of the measured hydroxylated polycyclic aromatic hydrocarbons corresponded on average to 28% of polycyclic aromatic hydrocarbons emissions. This study shows that wood combustion is a large emission source of hydroxylated polycyclic aromatic hydrocarbons and that not only combustion conditions, but also wood type influences the emissions of hydroxylated polycyclic aromatic hydrocarbons and polycyclic aromatic hydrocarbons. There are few studies that have determined hydroxylated polycyclic aromatic hydrocarbons in emissions from wood combustion, and it is therefore necessary to further investigate the formation, occurrence and distribution of these compounds as they are present in significant amounts in wood smoke particles. Highlights: Particulate OH-PAHs from residential wood log stove combustion were determined. Four different types of wood logs and two combustion conditions were examined. Pine burning in high burn rate had largest impact on particulate OH-PAH emissions. OH-PAH nominal burn rate emissions correspond to 15% of high burn rate emissions. Emissions of OH-PAHs correspond on average to 32% of PAH emissions.